The letter to the Romans as Paul’s legacy to theology: Reception in exposition - Breytenbach, Cilliers (Stellenbosch Theological Journal, 2017)
‘The Romans Debate’ fills not only volumes, but nowadays a bookshelf. In this paper I will neither argue in favour nor against this verdict of Bornkamm on the setting of Romans. Approaching his idea of the letter to the Romans as Paul’s legacy from reception history, I want to argue that the letter to the Romans became Paul’s legacy to Christian theology. In fact, it is the legacy of Paul. What I mean is that the reception of Paul’s theology is intertwined with the ‘Wirkungsgeschichte’ of the letter to the Romans. Pauline theology had its impact through the letter to the Romans.